ACTUALIZATION OF QS. AN-NAHL VERSE 125 AS A METHOD OF DA’WAH AND ITS RELEVANCE TO MODERNITY - Supardi (Universitas Islam Negeri Mataram, 2022)
Nowadays, preachers have a great responsibility for delivering da’wah. The da’wah method is one of the elements that have an important and strategic role because it supports the success of a da'i in conveying the message of da’wah. This paper analyzes one of the verses contained in Qs. An-Nahl verse 125 and its actualization in the era of modernity. This research uses descriptive qualitative methods. The findings of this study are the da’wah methods contained in QS. An-Nahl verse 125 and its relevance to modernity is still relevant and used by preachers in the modern era, because the method can be used at any time according to the times by adapting methods and materials to the level of understanding of mad’u.